Free residual DC voltage for nematic liquid crystals on solution-derived lanthanum tin oxide film. Issue 9 (15th July 2017) - Hyeon, Seung-Guk; Lee, Ju Hwan; Kim, Dong Hyun; Jeong, Hae-Chang; Oh, Byeong-Yun; Han, Jeong-Min; Lee, Jin-Woo; Seo, Dae-Shik
ABSTRACT: We present the liquid crystal (LC) alignment properties of solution-derived lanthanum tin oxide (LaSnO) films cured at various temperatures and exposed to ion-beam (IB) irradiation. Using a solution process, LaSnO films were deposited on the indium-tin-oxide glass substrates and IB irradiation was used as an alignment method. Homogeneous and uniform LC alignment was achieved and observed by cross-polarised optical microscopy. Pre-tilt angle results with low standard deviation supported the notion of uniform LC alignment. The LaSnO film cured at 300°C showed nearly zero capacitance–voltage hysteresis. The change of the surface morphology of the LaSnO film due to IB irradiation was observed by atomic force microscopy. The effects of IB irradiation on the LC alignment layer were further demonstrated by X-ray photoelectron spectroscopy. The strong IB irradiation broke the metal–oxide bonds present, which in turn induced an increased number of oxygen vacancies on the whole surface. Uniform LC alignment was attributed to surface reformation and van der Waals forces. Graphical Abstract: